The BH3 mimetic compound BH3I-1 impairs mitochondrial dynamics and promotes stress response in addition to its pro-apoptotic key function. (1st October 2018) - Stucki, David; Brenneisen, Peter; Reichert, Andreas S.; Stahl, Wilhelm
Graphical abstract: Highlights: BH3I-1 is a typical Bcl-2 antagonist and stimulates apoptosis. BH3I-1 additionally promotes mitochondrial fragmentation and HO-1 expression. The mitochondrial fission protein Drp-1 is linked to basal and inducible HO-1 levels. BH3I-1 effects on apoptosis are late events compared to its early effects on mitochondrial morphology and stress response. Abstract: BH3 mimetics, such as BH3I-1, act as Bcl-2 antagonists, promote apoptosis and are used in basic research studies on apoptotic signaling and are currently tested as experimental anti-tumor agents. The present study addresses time- and dose-dependent responses of BH3I-1 on apoptosis, cellular stress defense mediated by heme oxygenase-1 (HO-1), and mitochondrial morphology. As expected, treatment of normal human dermal fibroblasts with BH3I-1 induced apoptosis as determined by typical markers including cytochrome c release, loss of procaspase-3, and PARP cleavage. Induction of the cellular stress response marker HO-1 precedes apoptosis induction whereas fragmentation of the mitochondrial network was triggered even more rapidly. No difference in apoptosis induction was found upon depletion of HO-1 by siRNA compared to controls suggesting that apoptosis induction by BH3I-1 is not affected by HO-1. To evaluate the functional interplay between mitochondrial fragmentation and HO-1 induction, murine embryonic fibroblasts lacking the fission factor Drp1 were used. In Drp1 knock out cells, HO-1 levels were low compared to wild type cells, both in untreated controls as well as after BH3I-1 exposure, demonstrating that Drp1 is at least in part required for determining basal and inducible HO-1 levels. Considering the sequence of events, it was shown here that BH3I-1 dependent apoptosis is a rather late event, while effects on mitochondrial morphology and cellular stress response (HO-1 induction) are observed rapidly after exposure of cells to the compound. We propose that BH3I-1 is a valuable tool for studying cellular stress responses as well as mitochondrial dynamics in future studies. Since BH3 mimetics are promising experimental anticancer drugs, our data further imply that additional biological effects such as upregulation of detoxifying systems or changes in mitochondrial dynamics could interfere, in combination therapy, with selective drug toxicity and thus need to be taken into account for drug development.